Educação liberal, educação politécnica e ensino médio integrado: análise no IFCE - Matias, Maria Adellane Lopes (2019)
This research aimed to analyze the high school integrated in the Federal Institute of Science and Technology of Ceará (IFCE) as a proposal of education for youth. For its construction, we start from the study of the liberal and socialist educational proposals and their influences on the Brazilian education, trying to identify how they express themselves in the formation offered in the integrated high school of the referred teaching unit. The study has as its central categories polytechnics, vocational education and integrated high school. Politecnia is understood as one of the constitutive elements of socialist pedagogy, a pedagogical experience that took place in the Union of Soviet Socialist Republics (USSR) in the post-Revolution of 1917, with work as its educational principle as its central axis of formation. The category professional education addressed here refers to the education offered by the institutions of the Federal Network of Vocational Education, today represented by the Federal Institutes (IF's). In the debate on polytechnics we take as a reference mainly the studies of Pistrak (2009, 2011, 2015) and also contributions of the Russian pedagogue Krupskaya (2017). Regarding the category of professional education we subsidize the readings of Saviani (2007), Cunha (2000), Manfredi (2002), Kuenzer (2010), among others. For the integrated high school category we refer to the discussions made by Ramos (2010), Machado (2010), Frigotto (2012). In addition to these bibliographical references we subsidize documentary references about the laws and regulations that regulate the high school integrated in IFCE. The method of analysis used was historical-dialectical materialism by the investigative nature of the very elements that constitute our object. The research instruments used were bibliographic analysis and documentary analysis, taking into account the nature and purposes of the research. Among the results presented in that study, there is that in the proposal of integrated high school offered by IFCE, there is the presence of the elements of both the liberal proposal (in compliance with the precepts of pedagogy of competences) and the elements recommended by the polytechnic proposal, when It takes the work in its ontological sense, as an educational principle, foreseeing the formation in an integral perspective of the individual in its various dimensions, with the indissociability between the basic formation and the technical formation.